Medication Adherence and Lifestyle Modification in Pregnant Women with Hypertension - Sambas, Etty Komariah; Nurliawati, Enok; Setyarini, Wahyu Ikka (JURNAL KESEHATAN STIKes MUHAMMADIYAH CIAMIS, 2025)
Hypertension in pregnancy is a leading cause of maternal and fetal morbidity and mortality, contributing to 10% of global pregnancies and 412 maternal deaths in Indonesia in 2023. Proper management through medication and lifestyle changes is essential, but adherence remains low due to misinformation, fear of medication effects, and limited healthcare access. This study aimed to identify medication adherence and lifestyle modification in pregnant women with hypertension. A cross-sectional design was used with stratified random sampling. Data were collected through a validated questionnaire and analyzed descriptively. Results showed that 80.7% of respondents had high medication adherence and 77.2% had high lifestyle modifications. Significant associations were found between parity (p=0.042), history of hypertension (p=0.01), and ANC frequency (p=0.008) with medication adherence. Similarly, lifestyle modification was significantly associated with parity (p = 0.003), a history of hypertension (p = 0.000), and ANC frequency (p = 0.001). Multivariate analysis showed that ANC frequency predicted medication adherence (p=0.028), while history of hypertension predicted lifestyle modification (p=0.035). In conclusion, most pregnant women demonstrated high adherence levels. However, continuous health education, counseling, and family support are essential to maintain optimal maternal outcomes and reduce the risks associated with hypertensive disorders during pregnancy. Keywords : Hypertension, pregnancy, medication adherence, lifestyle modification.